1996
DOI: 10.1111/j.1365-2222.1996.tb00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and anaphylaxis induced by royal jelly

Abstract: Symptoms of asthma and anaphylaxis seen in subjects following ingestion of royal jelly were true IgE-mediated hypersensitivity reactions. The clinical significance of the antibodies found in the sera of control subjects is not known but they may arise in response to common inhalant allergens that show allergenic cross-reactivity with royal jelly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 17 publications
1
54
0
4
Order By: Relevance
“…1,2) Recently, however, a possibility that the royal jelly might have allergenicity for food-allergy patients has been reported. 3,4) Furthermore, it was reported that the N-glycans of a bee venom allergen, phospholipase A2, bear the Fuca1-3GlcNAcb1-Asn unit, 5) which shows strong antigenicity and has been postulated to be involved in allergic symptoms caused by food or pollen glycoallergens. 6,7) To conrm whether such antigenic N-glycans occur in the royal jelly glycoproteinous component, therefore, we started the structural analysis of total N-glycans linked to glycoproteins in royal jelly.…”
mentioning
confidence: 99%
“…1,2) Recently, however, a possibility that the royal jelly might have allergenicity for food-allergy patients has been reported. 3,4) Furthermore, it was reported that the N-glycans of a bee venom allergen, phospholipase A2, bear the Fuca1-3GlcNAcb1-Asn unit, 5) which shows strong antigenicity and has been postulated to be involved in allergic symptoms caused by food or pollen glycoallergens. 6,7) To conrm whether such antigenic N-glycans occur in the royal jelly glycoproteinous component, therefore, we started the structural analysis of total N-glycans linked to glycoproteins in royal jelly.…”
mentioning
confidence: 99%
“…Skin prick tests and provocation tests with royal jelly were positive [83]. Specific IgE binding to the allergens in the protein fraction of royal jelly, particularly to 55- and 47-kDa components, has been demonstrated [84]. However, in sera of allergic controls with a history of hay fever and eczema but with no known reaction to royal jelly as well as in bee-venom-sensitized patients, a similar pattern was also observed.…”
Section: Food-related Allergic Reactions From Insect Productsmentioning
confidence: 98%
“…However, in sera of allergic controls with a history of hay fever and eczema but with no known reaction to royal jelly as well as in bee-venom-sensitized patients, a similar pattern was also observed. The 55-kDa band could correspond to an earlier described major royal jelly protein [84]. …”
Section: Food-related Allergic Reactions From Insect Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,12) Human safety is an important factor to consider, because RJ is consumed as a dietary supplement. In this regard, it is noteworthy that untreated RJ has been reported to cause such adverse reactions as urticaria, eczema, acute asthma and anaphylaxis, [13][14][15][16][17][18][19][20][21] although such adverse reactions rarely happen. 18,22) Rosmilah et al 17) and Leung et al 19) have reported that RJsensitive subjects possessed IgE antibodies against a number of RJ proteins.…”
mentioning
confidence: 99%